LAYANAN BIMBINGAN KELOMPOK DARING DENGAN TEKNIK SOSIODRAMA TERHADAP SISWA SLOW LEARNER - Naufal Falih; Heris Hendriana; Ardian Renata Manuardi (IKIP Siliwangi, 2023)
The purpose of this study is to find out how Online Group Guidance Services With Sociodrama Techniques for Slow learner Students of class X students, how teachers and students respond to group guidance services with sociodrama techniques to slow learner students, and what obstacles are faced in implementing group guidance services with sociodrama techniques for class X slow learner studentss. The research method used is descriptive qualitative with the type of field research. Interviews, observations and documentation were the data collection tools used in this study. The subjects of the study were 6 students. This research found that 1) The implementation of group guidance services at SMK Teknikom Cikarang is already in line well and teachers can encourage students to be able to solve problems 2) slow learner factors in class X students of SMK Teknikom Cikarang, including not having a cellphone, no quota, and a long distance from school. 3) Efforts made are increasing motivation, creating an environmental atmosphere that.